Numerical Analysis of Shoreline Change in Plentong Beach, Indramayu Regency, Indonesia - Subiyanto; Michelle Levina; Bintang Azahra; Umar Abdurrahman; Defania Saqina Ramadhanti; Mega Laksmini Syamsuddin; Sudradjat Supian (International Journal of Quantitative Research and Modeling, 2026)
Shoreline change is one of the most visible and measurable indicators of coastal dynamics, reflecting the complex interactions among waves, currents, sediment transport, and coastal morphology. Understanding and predicting shoreline evolution are increasingly important for environmental sustainability, coastal infrastructure planning, hazard mitigation, and integrated coastal zone management, particularly in sedimentary, low-lying coastal environments that are vulnerable to erosion and flooding. This study applies a One-Line numerical model to analyze shoreline evolution at Plentong Beach, Indramayu Regency, Indonesia, over a one-year simulation period from 2026 to 2027. Shoreline displacement was computed along an 1150 m stretch of coastline using transects spaced at approximately 50 m intervals, allowing for detailed spatial assessment of shoreline response. The results reveal pronounced spatial variability in shoreline behavior, characterized by significant erosion at both ends of the coastline and marked accretion in the central segment. This pattern indicates the dominant influence of gradients in longshore sediment transport, suggesting that shoreline change at Plentong Beach is primarily governed by alongshore sediment redistribution rather than uniform coastal retreat or advance. The central accretion zone likely represents a sediment convergence area, while the eroding segments function as sediment source zones within the coastal system. Overall, the study demonstrates the applicability and usefulness of the One-Line numerical approach for short-term shoreline prediction on sedimentary, low-lying coasts. The findings contribute to a better understanding of coastal morphodynamic processes at Plentong Beach and provide valuable insights that can support evidence-based coastal management, erosion mitigation strategies, and sustainable planning along the northern coast of Java.